A holistic analysis on risks of post-disaster reconstruction using rstudio bibliometrix - Serter, Merve; Gumusburun Ayalp, Gulden (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Post-disaster reconstruction (PDR) is a complex and unpredictable process, especially concerning the construction sector, where understanding associated risks is increasingly vital. This study investigates and evaluates the present condition of post-disaster reconstruction risk (RoPDR) and discerns research trends and deficiencies in the domain via a systematic literature review (SLR) and bibliometric analysis. The Web of Science (WoS) was preferred for its extensive repository of pivotal research publications and its integrated analytical capabilities for producing representative data. This study performed a comprehensive bibliometric analysis of 204 peer-reviewed journal articles regarding the risks associated with post-disaster reconstruction from 1993 to 2024, utilizing the R statistical programming package RStudio Bibliometrix R version 4.3.1 to map the research landscape, identify literature gaps, and analyze rising trends. As a result of the analyses, the risks of post-disaster reconstruction were classified into four main clusters. Despite numerous studies exploring post-disaster reconstruction through diverse perspectives and methodologies, the associated risks of these projects remain inadequately analyzed. This inaugural bibliometric study in the realm of RoPDR utilizes novel techniques, such as the h-index, thematic mapping, and trend topic analysis, to attain a comprehensive understanding. Hence, the outcome of this study will aid scholars and practitioners in thoroughly comprehending the present condition and identifying prospective research directions. © 2024 by the authors.
Keywords: bibliometric analysis; construction industry; disaster risk reduction; earthquake; post-disaster reconstruction; resilience; RStudio; temporary housing